2018
DOI: 10.1155/2018/7591259
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence, Antimicrobial Susceptibility Pattern, and Associated Factors of Urinary Tract Infections among Adult Diabetic Patients at Metu Karl Heinz Referral Hospital, Southwest Ethiopia

Abstract: Urinary tract infection causes considerable morbidity in diabetic patients and if complicated, can cause severe renal damage and life-threatening infections. The escalating antimicrobial resistance rate among bacteria over the past years is another concern in the treatment of urinary tract infections. This study investigated the prevalence, antimicrobial susceptibility pattern of the isolates and associated factors of urinary tract infection among adult diabetic patients attending Metu Karl Heinz Referral Hosp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

12
44
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(60 citation statements)
references
References 16 publications
12
44
4
Order By: Relevance
“…Bacteriological studies usually revealed the involvement of Gram-negative enteric organisms such as E. coli, Klebsiella species, Enterobacter species, and Proteus species in causing UTI. 17,31,32 Similarly, the predominant numbers of pathogens isolated in our study were Gramnegative bacilli (71.8%). Similarly, they were the dominant causative agent of UTIs in Harar, Gondar, rural South India, Iraq, Nepal, Sudan, and Kuwait.…”
Section: Discussionsupporting
confidence: 60%
See 2 more Smart Citations
“…Bacteriological studies usually revealed the involvement of Gram-negative enteric organisms such as E. coli, Klebsiella species, Enterobacter species, and Proteus species in causing UTI. 17,31,32 Similarly, the predominant numbers of pathogens isolated in our study were Gramnegative bacilli (71.8%). Similarly, they were the dominant causative agent of UTIs in Harar, Gondar, rural South India, Iraq, Nepal, Sudan, and Kuwait.…”
Section: Discussionsupporting
confidence: 60%
“…Comparable findings have been reported in previous studies conducted in Addis Ababa (10.9%), 15 Debre Tabor (10.9%), 16 Hawassa (13.8%), 25 and Romania (12.0%). 9 However, this finding was relatively lower as compared to studies conducted in Harar (15.4%), 14 Addis Ababa (14.9%), 18 Gondar (17.8%), 26 Metu, Ethiopia (16.7%), 17 Nekemet, Ethiopia (16.5%), 27 and Sudan (19.5%). 13 It was much lower than reports from different parts of the world such as a study in Uganda (22.0%), 28 Kuwait (35%), 7 India (49.15%), 29 and Nepal (54.76%).…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…Mama M et al has reported that E.Coli are highly sensitive to amoxicillin and chloremphenicol but Klebsiella was sensitive to trimethoprime and erythromycin. 21,22…”
Section: Discussionmentioning
confidence: 99%
“…The successful therapy for urinary tract infection depends on the identification of microbial agents and the selection of antimicrobial against them (Gutema et al 2018).The mainbacteria associated with urinary tract infection in diabetes are Escherichia coli, Enterococcus spp., Klebsiella spp., Proteus spp., Pseudomonas aeruginosa, Staphylococcus aureus, and coagulase-negative streptococcus. Other studies showed that fungi, namely, Candida spp.…”
mentioning
confidence: 99%